unDerstandIng the cauSes of mediCation errOrs and adVerse drug evEnts for patients with mental illness in community caRe (DISCOVER): a qualitative study - Ayre, Matthew J.; Lewis, Penny J.; Phipps, Denham L.; Keers, Richard N. (Frontiers in Psychiatry, 2023)
It is estimated that 237 million medication errors occur in England each year with a significant number occurring in the community. Our understanding of the causes of preventable medication errors and adverse drug events (ADE) affecting patients with mental illness is limited in this setting. Better understanding of the factors that contribute to errors can support the development of theory-driven improvement interventions.Remote qualitative semi-structured interviews with 26 community-based healthcare professionals in England and Wales were undertaken between June-November 2022. Recruitment was undertaken using purposive sampling via professional networks. Interviews were guided by the critical incident technique and analysed using the framework method. Any data that involved speculation was not included in the analysis. Independent analysis was carried out by the research team to extract themes guided by the London Protocol.A total of 43 medication errors and 12 preventable ADEs were discussed, with two ADEs having an unknown error origin. Prescribing errors were discussed most commonly (n=24) followed by monitoring errors (n=8). Six contributory factor themes were identified: the individual (staff), the work environment, the teams/interfaces, the organisation and management, the patient, and the task and technology. The individual (staff) factors were involved in just over 80% of all errors discussed. Participants reported a lack of knowledge regarding psychotropic medication and mental illnesses which accompanied diffusion of responsibility. There were difficulties with team communication, particularly across care interfaces, such as ambiguity/brevity of information being communicated and uncertainty concerning roles which created confusion amongst staff. Unique patient social/behavioural contributory factors were identified such as presenting with challenging behaviour and complex lifestyles, which caused difficulties attending appointments as well as affecting overall clinical management.These findings highlight that the causes of errors are multifactorial with some unique to this patient group. Key areas to target for improvement include the education/training of healthcare professionals regarding neuropharmacology/mental illnesses and enhancing communication across care interfaces. Future research should explore patient perspectives regarding this topic to help develop a holistic picture. These findings can be used to guide future intervention research to ameliorate medication safety challenges for this patient group.